Factors causing road traffic accidents with particularly serious consequence - E. V. Pechatnova; V. N. Kuznetsov (Вестник СибАДИ)
Introduction. Reducing the number of road traffic fatalities and aiming for zero deaths by 2030 is a key road safety government goal. The prevention of especially serious road accidents is one of the elements of achieving this goal. Analysis of the main factors contributing to the especially serious road accidents occurrence is the basis of an effective system for their prevention. A review of the scientific literature reveals a lack of knowledge in this area.Materials and methods. The study was performed on the basis of especially serious road accidents sample. The accidents that occurred in the regions of the Siberian Federal District in the period from 2017 to 2020 were analyzed. The following parameters were analyzed: the number of dead and injured, the type of accident, the period of the day, the day of the week, the month of the year, the weather conditions and the condition of roadway. The study is based on a multidimensional frequency distribution. The calculations and graphs were made using MS Excel and Statistica.Results. The results are presented using 2D and 3D histograms and cross tables. An analysis of the especially serious road accidents structure made it possible to distinguish two groups of accidents that differ in the number of the injured and dead. The influence of the analysed factors contributing to the especially serious road accidents occurrence is determined.Practical importance. Knowledge of the factors influence on the frequency of especially serious road accidents occurrence will allow public services to effectively plan measures to prevent such accidents and respond to them. This will reduce the number of road accidents deaths.Originality. Two groups of road accidents with especially serious consequences are identified and substantiated. It was found that the factors have different effects on the distribution of accidents in these groups. The study contains new knowledge of the factors contributing to the especially serious road accidents occurrence.